Directions of arrival estimation for multi frequency-hopping signals based on digital channelized receiver and spatial time-frequency analysis - CHEN Li-hu; ZHANG Er-yang (Tongxin xuebao)
An algorithm of DOA estimation for multi frequency-hopping signals based on digital channelized receiver and spatial time-frequency analysis was proposed, which can realize exact DOA estimation in underdetermined condition. First, the architecture of digital channelized receiver based on polyphase filter banks was realized. Second, a clear time-frequency representation was gained by time-frequency analysis. Third, effective hops were selected from the time-frequency distribution, and every hop’s spatial time-frequency matrix was built. At last every hop’s DOA was estimated based on spatial time-frequency method. The simulation results demonstrate that the estimation algorithm is effective and efficient.